Kali Linux 2018 - Windows penetration testing : conduct network testing, surveillance, and pen testing on MS Windows using Kali Linux 2018 /: conduct network testing, surveillance, and pen testing on MS Windows using Kali Linux 2018. (2018) - Halton, Wolf; Weaver, Bo
No abstract available